The Arsenic Methylation Cycle: How Microbial Communities Adapted Methylarsenicals for Use as Weapons in the Continuing War for Dominance - Chen, Jian; Rosen, Barry P. (Frontiers in Environmental Science, 2020)
Arsenic is toxic and widely distributed in the environment. Most microorganisms have evolved mechanisms to use methylarsenicals as weapons in microbial warfare. This has created cycles of arsenic methylation and demethylation, which constitutes an important part of arsenic biogeochemical cycles and environmental health. Arsenic methylation forms methylarsenite [MAs(III)], arsenobetaine, arsenosugars and the new identified methylarsenical antibiotic, arsinothricin (AST). Bacteria use MAs(III) and AST as antibiotic to obtain a competitive advantage over other bacteria. Microbes produce toxic MAs(III) by (1) methylation of arsenite [As(III)] or (2) reduction of methylarsenate [MAs(V)]. In air, MAs(III) is oxidized to MAs(V) by oxygen, which conferring methylation to be considered as a detoxification pathway in aerobes. MAs(V) also can be re-reduced to MAs(III) by other bacteria, which can enable its survival and dominance with more competitive advantage than other sensitive bacteria. The different composition and diversity of microbial community could generate the sustained pool of MAs(III). These complex interactions have an emergent property., that is, overall scheme of arsenic-containing antibiotics emerges from interaction of multiple species. In response to production of the antibiotic MAs(III), other members of microbial communities have evolved at least four mechanisms for MAs(III) resistance: (1) ArsH detoxifies MAs(III) by oxidation to less toxic MAs(V); (2) ArsI degrades MAs(III) by cleavage of the C-As bond to form less toxic As(III); (3) the ArsP efflux permease confers selective resistance to MAs(III); and (4) the unrelated ArsK efflux permease confers resistance to both trivalent inorganic and organoarsenicals. Environmental application of anthropogenic aromatic arsenicals further fuels bacterial warfare and selection for novel resistance mechanisms. In another microbial adaptation to use environmental arsenic as a weapon, some soil bacteria synthesize a methylarsenate analog of the amino acid glutamic acid termed AST; AST shows a broad-spectrum antibiotic action against both Gram-negative and Gram-positive bacteria. In response to the environmental challenge presented by AST, arsN genes evolved to detoxify it by acetylation of the α-amino group. Thus, to battle for surviving and thriving in the microbial community, life has to adapted and use environmental arsenic as a weapon. Both MAs(III) and AST are natural products with antibiotic-like properties, both are toxic methylarsenicals produced by some microbe and further kill off its competitors, and resistances have arisen for both.